Differences in Value Systems of Anglo-American and Far Eastern Students: Effects of American Business Education - Kumar, Kamalesh (Journal of business ethics, 1998)
This study examined differences in the values patterns of business students from Anglo-American and Far Eastern country clusters using Allport et al.'s (1970) Study of Values. Differences were noted on five of the six attitudes; Theoretical, Economic, Political, Social, and Religious. Next, using multiple comparison method the value patterns of newly arrived Far Eastern students and Far Eastern students who had spent considerable time in the U.S. were compared for changes in value patterns that may be attributable to their stay and study in the United States. Differences were found in terms of five of the six evaluative attitudes between the two groups. Value pattern of Far Eastern students who had lived and studied in the U.S. for a considerable period of time was also compared with that of Anglo-American students to examine the degree of convergence in their value systems. Findings of this study suggest that as a result of frequent and sustained cross-cultural contacts in another cultural environment, the value profile of individuals tend to get modified, so as to include the values preferred and desired in the new social environment.